1997
DOI: 10.1021/ie970129q
|View full text |Cite
|
Sign up to set email alerts
|

On the Absorption of Isobutene and trans-2-Butene in Sulfuric Acid Solutions

Abstract: In reactions in which alkenes react in the presence of homogeneous Brønstedt acid catalysts, the protonation step is rate determining. Existing reaction rate correlations for protonation of butenes in sulfuric acid solutions are not consistent and limited to sulfuric acid concentrations below 80 wt %. The absorption of isobutene and trans-2-butene in sulfuric acid solutions was studied in the range of 30-98 wt %. Reevaluation of literature data, completed with new data from this study, revealed a set of kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Within the range 50-80 mass % H 2 SO 4 the deviations between model prediction and experimental determined data points are relatively large but still within 30% (which is relatively accurate if one considers that the protonation reaction rate constant varies over several decades in the range of acid concentrations). 1 The general trend is reasonably well described. This technique will be used for estimating the isobutene and trans-2-butene solubilities in aqueous sulfuric acid solutions.…”
Section: Estimation Of Solubility Of Gas-phase Components In Electrolmentioning
confidence: 70%
See 1 more Smart Citation
“…Within the range 50-80 mass % H 2 SO 4 the deviations between model prediction and experimental determined data points are relatively large but still within 30% (which is relatively accurate if one considers that the protonation reaction rate constant varies over several decades in the range of acid concentrations). 1 The general trend is reasonably well described. This technique will be used for estimating the isobutene and trans-2-butene solubilities in aqueous sulfuric acid solutions.…”
Section: Estimation Of Solubility Of Gas-phase Components In Electrolmentioning
confidence: 70%
“…When the above results and methods are used for interpretation of isobutene and trans-2-butene absorption fluxes in aqueous sulfuric acid solutions in order to retrieve kinetic data, 1 it is found that a significant part of the observed discrepancy in these kinetic data as found in the literature could be resolved.…”
Section: Diffusion Coefficientsmentioning
confidence: 97%
“…The reaction kinetics under Koch reaction conditions ( >75 wt.% H 2 SO 4 ) are not well known. Recent work [1] for the kinetics of the pivalic acid formation starting with isobutanol (and in a few experiments tert-butanol) as reactant has shown for these reactants that in absence of mass transfer limitations the carbocation formation is rate determining.…”
Section: Reaction Mechanism and Reaction Kineticsmentioning
confidence: 99%
“…In the industrially applied fully backmixed stirred tank reactors the hydrocarbon reactants and the acids produced constitute a dispersed organic liquid phase. Previous work has shown that the presence of the reaction product in the catalyst phase significantly affects the reaction kinetics [1]. The relatively small reactants used in this study, isobutene and tert-butanol, form a gas-liquid two-phase system with the sulfuric acid catalyst phase under the conditions studied.…”
Section: Introductionmentioning
confidence: 97%
“…The protonation of ole"ns leading to the same C carbocations, has been studied more frequently in literature, see e.g. Brilman, Swaaij and Versteeg (1997) for a recent overview and update of data for isobutene and trans-2-butene. In these cases the protonation kinetics depend strongly on the acid strength of the catalyst solution and a log-linear relationship between the apparent "rst-order (in the alcohol or alkene concentration) reaction rate constant for the protonation reaction and the Hammett acidity function Ho is found.…”
Section: The Carbocation Formationmentioning
confidence: 99%